Karakteristik Desa Migran Produktif yang Mempengaruhi Banyaknya TKI Bekerja ke Luar Negeri - Suryadi Suryadi (Jurnal Ketenagakerjaan, 2018)
The decrease of Indonesian Migrant Workers (TKI) working abroad, brings its own problems. One of the problems faced is the emergence of new unemployment as a result of the lack of existing jobs. For that, the government seeks to create new jobs in the country through the formation of Desmigratif. This research aims to determine the effect of productive migrant village characteristics on the number of migrant workers who work abroad. The influence of each independent variable such as variable of X 6 (existence of cooperative), variable of X 13 (number of types of economic means in the village), variable of X 15 (population of productive age) and variable of X 18 (territorial, Java and outside Java) to the dependent variable Y (the number of migrant workers working abroad). Resources, facilities and infrastructure of economic activities in productive migrant villages are very heterogeneous. The village government must have seriousness in making development policy to support community empowerment program, so that people will stay in the village, get a job or economic business, have income and prosperous, so do not leave their village to work abroad become TKI. All stakeholders in this program need to cooperate in identifying problems, mapping the potential of natural resources, people, culture, and village economics to become capital for development of productive migrant village.